A novel CYP17A1 deletion causes a functional knockout of the steroid enzyme 17‐hydroxylase and 17, 20‐lyase in a Turkish family and illustrates the precise role of the CYP17A1 gene. Issue 10 (26th August 2015) - Camats, Núria; Üstyol, Ala; Atabek, Mehmet Emre; Dick, Bernhard; Flück, Christa E.
Key Clinical Message A novel homozygous long‐range deletion of the CYP17A1 gene abolished protein expression and caused the severest form of 17‐hydroxylase deficiency in one kindred of a Turkish family. The affected subjects presented with 46, XY sex reversal and 46, XX lack of pubertal development as well as severe hypertension.